Interface end theory and re-evaluation in interfacial strength test methods - Ji, X.; Dai, Y.; Zheng, B.; Ye, L.; Mai, Y.
The experimental results of fragmentation, micro-indentation, pull-out and microdebond tests often exhibit large discrepancies. Since all specimens of the four test methods all have interface ends, the singularity theory of the interface end should be used to evaluate the exactness of the test methods. The eigenvalues of the specimens for the micro-indentation test, pull-out test and microdebond test are calculated and investigated. The results show that the stress singularity of the interface end depends on the Dundurs' parameters and the wedge angles. The interfacial shear strength (IFSS)obtained from the tests loses its rationality if the stress is singular at the interface end. In further analysis, for a carbon . ber-epoxy resin composite, it is found that the microdebond test gives the most reliable IFSS results, if the wedge angle of the resin droplet is less than 40±; the results from the pull-out test are dubious, due to the stress singularity at the interface end. In the icro-indentationtest, there is a criticalmatrix stiffness value for a given . ber, above which the stress at the interface end will be non-singular. The fragmentation test assumes the interfacial shear stress on the . ber fragment of critical length is the IFSS. If debonding does not occur at the interface end, then apparently, the interfacial shear stress on the . ber fragment of critical length is less than the true value of IFSS.
Keywords: INTERFACE; IFSS; STRESS SINGULARITY